Answer:
No please! Mr excuse me I am not your type bye
First, let's simplify each expression by combining like terms:
A: 9x-3x-4 = 6x-4
B: 12x-4 = 12x-4 (Already Combined terms)
C: 5x+x-4 = 6x-4
When looking at the list of equations, it is clear that only Expression A and C are equivalent. Brianna failed to combine like terms and plug in more points than 0.
I Hope this Helps!
-Sinnamin
Answer:
y = 4/9 x + 4
Step-by-step explanation:
Slope intercept form: y = mx = b
So 4x - 9y = -36
9y = 4x+ 36
y = 4/9 x + 4
155 = 2x -15
170 = 2x
85 = x
She had 85 when she first started.